Optic Perineuritis and Its Association With Autoimmune Diseases - Li, Hongyang; Zhou, Hang; Sun, Jiao; Wang, Huihui; Wang, Yanling; Wang, Zhenchang; Li, Jing (Frontiers in Neurology, 2021)
Background: Optic perineuritis (OPN) is a special optic neuropathy that has a distinct etiology from neuromyelitis optica spectrum disorders (NMOSDs) or multiple sclerosis (MS)-related optic neuritis (ON). The mechanisms of how this inflammation developed and invaded the nerve sheath remain unknown. This study is aimed to analyze the etiology and different clinical characteristics of OPN in a Chinese patient population. Methods: Neuro-ophthalmological examination, orbit magnetic resonance imaging (MRI) and a series of blood samples were used in this retrospective observational cohort study to compare characteristics of OPN with idiopathic demyelination optic neuritis (IDON). Results: Forty-four OPN cases (74 eyes) and 61 IDON cases (78 eyes) were analyzed. OPN cases included 33 cases (59 eyes) were associated with specific autoimmune diseases, 10 cases (13 eyes) were associated with infection diseases, 1 case was idiopathic disease. The causes of OPN with CTD were Graves' disease, Immunoglobulin G4-related disease (IgG-4 RD), granulomatosis with polyangiitis (GAP), systemic lupus erythematosus (SLE), Sarcoidosis, Rheumatoid arthritis, scleroderma, Behcet's disease, and gout. All patients received orbital MRI. Overall, 33 cases showed orbit fat infiltration. Specifically, nine cases with IgG-4 RD showed trigeminal nerve branch involvement, 12 cases with Graves' disease showed extraocular muscle belly enlargement, and 4 cases with GAP showed pterygopalatine fossa pseudotumor. Compared to IDON patients, OPN patients were older (p = 0.004) and more likely bilateral involvement 26 (78.79%) patients had bilateral involvement in OPN group vs. 17 (27.87%) in the IDON group (p < 0.001). Visual acuity scores using LogMAR testing was better in OPN patients compared to those with IDON, 0.55 ± 0.91 vs. 1.19 ± 1.24 (p < 0.001). Other ophthalmologic findings unique to the OPN group include 11 (33.33%) cases of ptosis, nine (27.27%) cases of diplopia, and 10 (30.30%) cases of exophthalmos, compared to zero cases of these conditions in the IDON group. Eight (13.11%) IDON patients also had multiple sclerosis (MS) and 7 (11.48%) patients had neuromyelitis which was significantly more than the zero patients in OPN group (p = 0.04). Conclusions: OPN had distinct etiologies and clinical characteristics from IDON and is more often associated with autoimmune diseases. Using OPN characteristics to diagnose autoimmune diseases should prove useful for clinicians when presented with patients that have multiorgan dysfunction that include ophthalmologic findings.